Developing Citizen Relationship Management (CiRM) Oriented E-Government Maturity Model - Anita Wulansari; Apol Pribadi Subriadi (Institut Teknologi Sepuluh Nopember, 2017)
CiRM (Citizen Relationship Management) has an important role in the government because it puts citizen in the best interests. So far the implementation of e-government only focused on the technology assimilation process. Since existing e-government maturity assessment models only measure the ability of e-government technology, they lack in consideration towards citizen needs. Therefore an e-government maturity assessment model is developed by incorporating elements of CiRM. The model was developed through a grounded theory qualitative study approach. The object of this research is e-government application owned by the city of Surabaya. This research developed CiRM oriented e-government maturity model consisted of organization, interaction, service and citizen insight dimensions. This model then was used to assess the maturity of CiRM oriented e-government implementation of Surabaya Single Window (SSW) online service.